Critical Infrastructure Resilience - National Approaches in the USA, the United Kingdom and Australia - Ninkovic, Vladimir (Zbornik radova Pravnog fakulteta u Novom Sadu, 2022)
Securitization of the critical infrastructure as an important factor of the national security has been among the aspects of wider changes in the security discourse since the end of the Cold War, and especially since the 9/11 attack. The concept of critical infrastructure protection, initially focused on countering the terrorism threat, has been moving and expanding, from adopting the ‘all-hazard approach’, until the recent popularity of the strategy of resilience. The paper discusses the concepts of resilience and critical infrastructure, and then analyses the approaches to critical infrastructure protection and resilience in the United States, the United Kingdom and Australia. The paper analyzes the official documents – strategies, laws and by-laws, reviews and guidelines produced by the governmental bodies of the mentioned countries, with the aim of clarification of the concept, as well as the country-specific variations in its operationalization.
Keywords: critical infrastructure, resilience, all-hazard approach, risk management, national security